Can intellectual property be used to halt global biodiversity loss? - Andrea Alunni (Revista de Fomento Social, 2022)
Biodiversity loss is the single biggest negative consequence from environment degradation. Access and beneﬁt sharing (ABS) – stipulated by the Convention on Biological Diversity (CBD) and established under Nagoya protocol (NP) – is a policy approach that links access to genetic resources (GR) and traditional knowledge (TK) to the sharing of monetary and nonmonetary beneﬁts. This article examines how the ABS has become the principal instrument embraced by the international fora to prevent further biodiversity loss by avoiding GRs extinction and/or degradation, often due to the misuse and misappropriation of TK associated to GR management. The objective of this research is to analyse the process in which traditional knowledge associated to the management of genetic resources (TK–GR) came onto the Intellectual Property (IP) agenda and to verify whether ABS can effectively regulate the access to the world’s GRs while contributing to the conservation of biological diversity and the sustainable use of its components in a way that is acceptable to all stakeholders. The research was carried out in two parts: The ﬁrst, explores the literature that outlines the evolution of the IP policy debate in which the IP–TK–GR linkage was recognised as having signiﬁcant implications to avoid biodiversity loss by preserving TK holders’ role in a rapid evolving biotechnology innovation environment. This was conducive to the second part which assesses the governance in relation to TK–GR protection together with the challenges and opportunities that international institutional and political frameworks face to support ABS adoption across countries. A practical example illustrates how indigenous peoples and local communities’ skills can be embedded in technology transfer best practices to effectively adopt ABS to produce new knowledge, innovation and prosperity from joint research and cooperation between traditional and modern scientists.